Iran-Saudi-Turkish Rivalry and Implications of the Iran-US/West Nuclear Agreement on Wahabis in Indonesia - Herdi Sahrasad; Al Chaidar; Muhammad Ridwan; Dedy Tabrani; Mohamad Asrori Mulky (Britain International for Academic Research (BIAR) Publisher, 2020)
A world agreement on Iran's Nuclear was reached in Vienna, Austria, in July 2015. Negotiations between Iran and the six world powers namely the United States, Britain, France, China, Russia plus Germany began in 2006 and reached an agreement with Iran at the Vienna Meeting in July 2015 in an effort to reduce Iran's nuclear activities in exchange for lifting sanctions or embargoes. international economy that has lasted three decades. United States President Barack Obama (2015) said that with the agreement that opened the new page, all Iranian nuclear weapons had been cut off for Iran so that the Middle East nuclear power was held militarily by Israel. In this regard, international sanctions against Iran are lifted, and Iran has a stronger chance to improve its posture in the international arena. The Vienna Agreement has caused ideological anxiety among Wahabis with the implication that Wahabis are unhappy and they do not like the strengthening of Iran politically and culturally in a globalized world. Wahhabi ideological interests will be eroded to some extent by treaties that will seriously divide the Islamic world by Sunni-Shiite competition. However, the rise of Turkey which is competing with Iran and Saudi Arabia in the Middle East political arena, will open the eyes of Wahabis in Indonesia that it is very likely Turkey is their hope for the future.